Antimicrobial Prophylaxis and Modifications of the Gut Microbiota in Children with Cancer - Gianluca Bossù; Riccardo Di Sario; Alberto Argentiero; Susanna Esposito (MDPI AG, 2021)
In children with cancer, chemotherapy can produce cytotoxic effects, resulting in immunosuppression and an augmented risk of febrile neutropenia and bloodstream infections. This has led to widespread use of antibiotic prophylaxis which, combined with intensive chemotherapy treatment, could have a long-term effect on the gastrointestinal microbiome. In this review, we aimed to analyze the current literature about the widespread use of antibiotic prophylaxis in children experiencing infectious complications induced by chemotherapy and its effects on the gut microbiome. Our review of the literature shows that antimicrobial prophylaxis in children with cancer is still a trending topic and, at the moment, there are not enough data to define universal guidelines. Children with cancer experience long and painful medical treatments and side effects, which are associated with great economic and social burdens, important psychological consequences, and dysbiosis induced by antibiotics and also by chemotherapy. Considering the importance of a healthy gut microbiota, studies are needed to understand the impact of dysbiosis in response to therapy in these children and to define how to modulate the microbiome to favor a positive therapeutic outcome.